Gain enhancement in partial double-pass L-band EDFA system using a band-pass filter - Harun, S. W.; Md Samsuri, N.; Ahmad, H. (2005)
The partial double-pass L-band erbium-doped fiber amplifier with enhanced gain characteristic is demonstrated using a baud pass filter (BPF). The BPF is incorporated in the double-pass route to suppress the amplified spontaneous emission from the single-pass output for gain enhancing. The gain of 51.5 dB is obtained for the proposed amplifier at input signal power of -40 dBm, which is approximately 5.2 dB higher compared with the system without the BPF. However, the insertion loss of the BPF contributes to a small noise figure penalty in the system. This amplifier can be easily modified to support dense wavelength division multiplexing system application by using multiple channel BPFs or interleaver.